Spawning habitat selection and behavioural repeatability of stocked Walleye (Sander vitreus) in Hamilton Harbour - Paul A. Bzonek; Melanie V. Croft-White; David T. Reddick; Nicole A. Turner; M. Cole MacLeod; Steven J. Cooke; Jill L. Brooks; Caleb T. Hasler; Jonathan D. Midwood (Aquatic Sciences, 2026)

Comparison of black carbon media for removal of dissolved metals in stormwater - Kristen Croft; Sabrina De Nicola; Chen Yuan; Devrim Kaya; Allen P. Davis; Birthe V. Kjellerup (Journal of Contaminant Hydrology, 2026)

Treatment of polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) in stormwater using polishing columns with biochar and granular activated carbon - Chen Yuan; Kristen Croft; Sabrina de Nicola; Allen P. Davis; Birthe V. Kjellerup (Chemosphere, 2025)

Diversity of movement patterns of Longnose Gar tracked in coastal waters of western Lake Ontario - Melanie V. Croft-White; Sarah M. Larocque; David T. Reddick; Paul D. Smith; Steven J. Cooke; Jonathan D. Midwood (Environmental Biology of Fishes, 2024)
Understanding the spatial ecology of fish is critical for effective conservation and management. Gar (Lepisosteidae spp.) are an ancient lineage of freshwater fishes that have long been thought of as having high site fidelity with limited large-scale movements. We acoustically tagged Longnose Gar ( L. osseus ) in a large freshwater embayment (Hamilton Harbour) and tracked the movements of 12 individuals within this system and throughout the coastal waters of Lake Ontario for up to 4 years. Three distinct movement patterns were observed: migrants ( N = 7), which moved throughout much of western Lake Ontario and had a maximum displacement of 184 km (linear distance); residents ( N = 3), which remained in or near the original tagging location (an industrial slip with year-round warmwater outfall); and sporadic migrants ( N = 2), which showed both migratory and resident behavioural patterns in different years. Seasonally, gar were most active during the summer and then fall, with more restricted home ranges and movements during winter suggestive of more quiescent behaviour. This study represents the first use of acoustic telemetry to track Longnose Gar movements year-round in a large lake and confirmed that a majority of tracked fishes make large-scale movements in Lake Ontario. Such results reframe the presumption that gar are more resident fishes with restricted space use.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Interactions of particulate- and dissolved-phase heavy metals in a mature stormwater bioretention cell - Kristen Croft; Birthe V. Kjellerup; Allen P. Davis (Journal of Environmental Management, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: Fish composition, but not richness or abundance, differ among Phragmites, Typha, and Schoenoplectus zones during a high-water year - M. V. Croft-White; E. Budgell; C. Jacobs; S. E. Doka; D. T. Reddick; J. Gardner Costa; J. D. Midwood (Hydrobiologia, 2021)

Fish composition, but not richness or abundance, differ among Phragmites, Typha, and Schoenoplectus zones during a high-water year - M. V. Croft-White; E. Budgell; C. Jacobs; S. E. Doka; D. T. Reddick; J. Gardner Costa; J. D. Midwood (Hydrobiologia, 2021)

Comparative population genomics reveals key barriers to dispersal in Southern Ocean penguins - Gemma V. Clucas; Jane L. Younger; Damian Kao; Louise Emmerson; Colin Southwell; Barbara Wienecke; Alex D. Rogers; Charles‐André Bost; Gary D. Miller; Michael J. Polito; Patrick Lelliott; Jonathan Handley; et al. (Molecular Ecology, 2018)
The mechanisms that determine patterns of species dispersal are important factors in the production and maintenance of biodiversity. Understanding these mechanisms helps to forecast the responses of species to environmental change. Here, we used a comparative framework and genomewide data obtained through RAD ‐Seq to compare the patterns of connectivity among breeding colonies for five penguin species with shared ancestry, overlapping distributions and differing ecological niches, allowing an examination of the intrinsic and extrinsic barriers governing dispersal patterns. Our findings show that at‐sea range and oceanography underlie patterns of dispersal in these penguins. The pelagic niche of emperor ( Aptenodytes forsteri ), king ( A. patagonicus ), Adélie ( Pygoscelis adeliae ) and chinstrap ( P. antarctica ) penguins facilitates gene flow over thousands of kilometres. In contrast, the coastal niche of gentoo penguins ( P. papua ) limits dispersal, resulting in population divergences. Oceanographic fronts also act as dispersal barriers to some extent. We recommend that forecasts of extinction risk incorporate dispersal and that management units are defined by at‐sea range and oceanography in species lacking genetic data.

Are Toronto’s streams sick? A look at the fish and benthic invertebrate communities in the Toronto region in relation to the urban stream syndrome - Angela M. Wallace; Melanie V. Croft-White; Jan Moryk (Environmental Monitoring and Assessment, 2013)

Acute dopamine and/or serotonin depletion does not modulate mismatch negativity (MMN) in healthy human participants - Sumie Leung; Rodney J. Croft; Valérie Guille; Kirsty Scholes; Barry V. O’Neill; K. Luan Phan; Pradeep J. Nathan (Psychopharmacology, 2010)

Behavioral responses of humpback whales (Megaptera novaeangliae) to whale-watching vessels on the southeastern coast of Australia - Kasey A. Stamation; David B. Croft; Peter D. Shaughnessy; Kelly A. Waples; Sue V. Briggs (Marine Mammal Science, 2009)

Non-random sampling and its role in habitat conservation: a comparison of three wetland macrophyte sampling protocols - Melanie V. Croft; Patricia Chow-Fraser (Biodiversity and Conservation, 2009)

Evidence for modulation of facial emotional processing bias during emotional expression decoding by serotonergic and noradrenergic antidepressants: an event-related potential (ERP) study - Rebecca Kerestes; Izelle Labuschagne; Rodney J. Croft; Barry V. O’Neill; Zubin Bhagwagar; K. Luan Phan; Pradeep J. Nathan (Psychopharmacology, 2009)

Acute high-dose glycine attenuates mismatch negativity (MMN) in healthy human controls - Sumie Leung; Rodney J. Croft; Barry V. O’Neill; Pradeep J. Nathan (Psychopharmacology, 2008)

High-dose glycine inhibits the loudness dependence of the auditory evoked potential (LDAEP) in healthy humans - Barry V. O’Neill; Rodney J. Croft; Sumie Leung; Chris Oliver; K. Luan Phan; Pradeep J. Nathan (Psychopharmacology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Dopamine receptor stimulation does not modulate the loudness dependence of the auditory evoked potential in humans - Barry V. O’Neill; Rodney J. Croft; Sumie Leung; Valérie Guille; Matthew Galloway; K. Luan Phan; Pradeep J. Nathan (Psychopharmacology, 2006)

Intra- and interspecific predation by adult female Metaseiulus occidentalis and Typhlodromus pyri (Acari: Phytoseiidae) when provisioned with varying densities and ratios of Tetranychus urticae (Acari: Tetranychidae) and phytoseiid larvae - I. V. MacRae; B.A. Croft (Experimental and Applied Acarology, 1997)